2000
DOI: 10.1016/s0304-3959(99)00243-2
|View full text |Cite
|
Sign up to set email alerts
|

Debilitating chronic pain syndromes after presumed intraneural injections

Abstract: This report presents seven patients with severe disability established at the time of a peripheral nerve block. In most of the cases, the injection was administered as a routine procedure by an experienced anesthesiologist. The patient histories suggest that the condition, which can be resistant to all treatment, in most cases could have been avoided if careful attention had been given to the occurrence of pain during the nerve block. It is likely that the risk of devastating iatrogenic disability can be minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…9,10 Constant evolution of the number of procedures and unknown mechanisms underline the importance of a rigorous block sequence, particularly during a multi-stimulation technique. This is emphasized by the poor outcome of chronic neurological disabilities following peripheral nerve blocks, 11 and the fact that no study has demonstrated that neurostimulation reduces neurological complication rates. 12 Finally we must emphasize the importance of the local anesthetic used.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…9,10 Constant evolution of the number of procedures and unknown mechanisms underline the importance of a rigorous block sequence, particularly during a multi-stimulation technique. This is emphasized by the poor outcome of chronic neurological disabilities following peripheral nerve blocks, 11 and the fact that no study has demonstrated that neurostimulation reduces neurological complication rates. 12 Finally we must emphasize the importance of the local anesthetic used.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…Symptoms mostly are moderate and transitory with a tendency of spontaneous recovery within times related to nerve regeneration and repair mechanisms. Interestingly, Kaufman et al [24 ] reported a series of seven patients suffering from severe, debilitating chronic pain states after peripheral nerve blocks. However, in the present study there was one case of neuropraxia and weakness in radial nerve distribution of the blocked arm post operatively.…”
Section: Discussionmentioning
confidence: 99%
“…14 Symptoms mostly are moderate and transitory with a tendency of spontaneous recovery within times related to nerve regeneration and repair mechanisms. Interestingly, Kaufman et al, 15 reported a series of seven patients suffering from severe, debilitating chronic pain states after peripheral nerve blocks. In all seven cases, painful paraesthesia were elicited at the time of nerve block, be they voluntary or accidental with a progress to severe chronic pain condition.…”
Section: Discussionmentioning
confidence: 99%